IMPLEMENTASI PACKAGING STRATEGY GUNA MENINGKATKAN DAYA SAING PADA PELAKU UMKM DI DESA BUNUT, PESAWARAN - siti ulfa nabila; Hidayati Sholiha Jamil; Putri Azizah (Journal of Social Outreach, 2023)
Packaging is the activity of designing and producing a container or wrapper as a product. The purpose of the packaging strategy is to produce packaging that is attractive, easy to carry, safe, does not cause food contamination, and provides complete and adequate product information. Good packaging can boost sales of a product. This Community Service uses the coaching clinic method, which is a combination of three indicators (counseling, mentoring and evaluation). The result of this research is that the implementation of packaging strategy is able to increase the sales competitiveness of a product. Good packaging is a means of communication that helps increase sales, over time packaging has evolved its function which was originally only aimed at protecting a product, now has a broader function, one of which is branding or product identity. Keywords: UMKM, Packaging strategy, Competitiveness